Influence of Deep Margin Elevation and preparation design on the fracture strength of indirectly restored molars. (October 2020) - Bresser, R.A.; van de Geer, L.; Gerdolle, D.; Schepke, U.; Cune, M.S.; Gresnigt, M.M.M.
Abstract: The objectives of this in-vitro study were to investigate the influence of Deep Margin Elevation (DME) and the preparation design (cusp coverage) on the fracture strength and repairability of CAD/CAM manufactured lithium disilicate (LS2 ) restorations on molars. Sound extracted human molars (n = 60) were randomly divided into 4 groups (n = 15) (inlay without DME (InoD); inlay with DME (IWD); onlay without DME (OnoD); onlay with DME (OnWD)). All samples were aged (1.2 × 10 6 cycles of 50N, 8000 cycles of 5–55 °C) followed by oblique static loading until fracture. Fracture strength was measured in Newton and the fracture analysis was performed using a (scanning electron) microscope. Data was statistically analyzed using two-way ANOVA and contingency tables. DME did not affect the fracture strength of LS2 restorations to a statistically significant level (p = .15). Onlays were stronger compared to inlays (p = .00). DME and preparation design did not interact (p = .97). However, onlays with DME were significantly stronger than inlays without DME (p = .00). More repairable fractures were observed among inlays (p = .00). Catastrophic, crown-root fractures were more prevalent in onlays (p = .00). DME did not influence repairability of fractures or fracture types to a statistically significant level (p > .05). Within the limitations of this in-vitro study, DME did not statistical significantly affect the fracture strength, nor the fracture type or repairability of LS2 restorations in molars. Cusp coverage did increase the fracture strength. However, oblique forces necessary to fracture both inlays and onlays, either with or without DME, by far exceeded the bite forces that can be expected under physiological clinical conditions. Hence, both inlays and onlays are likely to be fracture resistant during clinical service.